2018
DOI: 10.3934/microbiol.2018.2.347
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological safety of flours used in follow up for infant formulas produced in Ouagadougou, Burkina Faso

Abstract: The prevalence of diarrheal diseases in children aged from 6 to 24 months in Burkina Faso is 38%. These diarrheas may be due to the consumption of contaminated weaning food. Therefore, the microbiological quality of follow up infant flours used as supplement foods is a key-point to reduce children diseases. In this study, the microbiological safety of locally-produced infant flours was investigated. One hundred and ninety-nine (199) samples were collected mainly in retails outlets and in Recovery and Nutrition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…They further reported that some species of Aspergillus found in the flour were capable of producing mycotoxins. Some of the fungal isolates reported by Waré et al (2018) were also identified in soybean flour sampled from four markets in Benin City. Among the fungal isolates encountered in the soybean flour either exposed or packaged, A. niger had the highest frequency of occurrence (23%).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…They further reported that some species of Aspergillus found in the flour were capable of producing mycotoxins. Some of the fungal isolates reported by Waré et al (2018) were also identified in soybean flour sampled from four markets in Benin City. Among the fungal isolates encountered in the soybean flour either exposed or packaged, A. niger had the highest frequency of occurrence (23%).…”
Section: Discussionmentioning
confidence: 87%
“…In a related study, Waré et al (2018) reported the presence of Mucor sp., Penicillium sp., Fusarium verticillioides, A. flavus, Aspergillus carbonarius, Aspergillus tamari, A. oryzae and Aspergillus sydowii in exposed flours used in formulating weaning food. They further reported that some species of Aspergillus found in the flour were capable of producing mycotoxins.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations